Renewable Woman: A Gender Analysis of Kidung Tresna Sang Pikatan and Prau Layar ing Kali Code - Rahayu, Wiwien Widiyawati; Yudha Adhistira; Hidayah, Saktia (MOZAIK HUMANIORA, 2025)
Women in the past are reconstructed by both male and female authors into positioned subjects. The transformation of women from object to subject is recorded in two Javanese novels of the Reformation era that become the material object of this research, namely Kidung Tresna Sang Pikatan and Prau Layar Ing Kali Code. Aspects of women’s subjectivation in these Javanese novels are identified, categorized and analyzed by applying the concept of gender, which views the resistance of female characters in literary works as an effort  to negotiate how  women  should be positioned. In both novels, the analysis will focus on two characters, Wulan in Kidung Tresna Sang Pikatan and Gandawati in Prau Layar Ing Kali Code. Both characters are characterized by their dominance over me. To see this phenomenon, the author tries to apply Haraway’s view of critical feminism and the concept of cyborg. The research proves that women have an important role in both narratives built by the author in the transformative novel that is sourced from historical stories and pre-existing myths.